IMPLEMENTASI DIGITAL MARKETING DALAM ERA SOCIETY 5.0 - Jelanti, Desi; Nursita, Meta; Napisah, Napisah; Khuliqi, Khusnul; Pratomo, Nugroho Widhi (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2021)
Digital marketing becomes a new prima donna in the business world is not without reason, digital marketing has some value more when compared to other promotional strategies. With the use of digital marketing manufacturers can market their products faster, easier, cheaper and also with a much wider reach because the virtual world seems to know no borders and time. Indonesia is "a sleeping Asian digital technology giant". The population of Indonesia which reaches 250 million people is a large market. Indonesian smartphone users are also growing rapidly. Emarketer digital marketing research institute estimates that in 2018 the number of active smartphone users in Indonesia is more than 100 million people. With such a large number, Indonesia will become the country with the fourth largest active smartphone users in the world after China, India, and America. UNPAM opened itself to conduct various cooperation with various parties in the framework of the development of science, institutions, technology and art in the framework of the implementation of Tri Dharma Higher Education, namely Education, Research and Devotion. UNPAM already has a network with various other institutions, namely the central government, provincial government, district government, business world, private sector and with the community. Boarding schools independent santri building institutions are one of the boarding schools that are quite unique, because usually boarding schools only focus on religious education only, but boarding schools independent santri institutions not only focus on religious education, but also education about entrepreneurship as a provision of santriwan and santriwati to make a living in the world.  Therefore, almost all managers and santriwan and santriwati in the peantren hut are entrepreneurs. The implementation of community service in the boarding school is expected to be able to help entrepreneurs to increase their sales through digital marketing strategies.